Unveiling the State of Mental Health in Finland: Insights, Challenges, and Pathways to Well-Being - Lampinen Mishina; Lilja Eino (GoAcademica Research & Publishing, 2023)
In the serene landscapes of Finland, a nation renowned for its quality of life, this journal article delves into the intricate tapestry of mental health. Titled